2005
DOI: 10.1363/3108305
|View full text |Cite
|
Sign up to set email alerts
|

Wealth and Extramarital Sex Among Men in Zambia

Abstract: CONTEXTSeveral studies have examined factors associated with the likelihood of having sexual relationships outside of marriage. These studies were mostly designed to answer questions on some aspects of marital infidelity, cultural values and norms of the societies under study. For example, in the United States, the emphasis has been on how marital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 18 publications
6
41
4
Order By: Relevance
“…Consistent with the findings of other studies [36-39], we found associations between several other factors and extramarital sex. Having first sexual intercourse before 16 years of age was a predictor of extramarital sex compared to having the first sexual intercourse after 16.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the findings of other studies [36-39], we found associations between several other factors and extramarital sex. Having first sexual intercourse before 16 years of age was a predictor of extramarital sex compared to having the first sexual intercourse after 16.…”
Section: Discussionsupporting
confidence: 93%
“…Education and wealth index were both found to be significantly associated with having extramarital sexual relationships. This finding has not been consistent across the board [36,41]. While no association was found between socio-economic status and extramarital sexual relationships in Zambia [36] this was found to be the case in the United States of America [41].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The signs of the coefficients were as expected given the arguments and findings of previous studies outlined in Section 3; however, it is important to note that no regular patterns related to the role of religious affiliation and the type of marriage were observed in the literature (Isiugo-Abanihe 1994;Carael, Ali, and Cleland 2001;Kimuna and Djamba 2005;Reniers and Tfaily 2008;Clark 2010). According to Models 1 and 2, age, education, risk perception, duration of marriage, and having spent at least one month outside of the district did not have a statistically significant influence on men's extramarital behavior.…”
Section: Empirical Analysissupporting
confidence: 81%
“…The influence of religion appears to differ depending on the country (IsiugoAbanihe 1994; Kimuna and Djamba 2005;Clark 2010). The indicator used in this study synthesized the different faiths into four categories: Muslim, Catholic, Protestant, and others.…”
Section: Data and Measuresmentioning
confidence: 99%